DESIGN OF PUSH-IN PILE FOUNDATION, SECANT PILE WALL WITH STEEL STRUTTING, AND AMPHITHEATRE EXCAVATION FOR PUBLIC LIBRARY WITH ELEVATED WALKWAY IN KELAPA GADING - Rhein Panuturi Gurning, David
The Kelapa Gading Roundabout Area with its densely habited space and full of commercial activities opens a potential for a new public facility in the form of a library that can trigger people to meet and interact. The library is a reinforced concrete building that consists of four floors above ground with the maximum elevation of 19m and two levels of basement with a total depth of 7m. To increase the accessibility of pedestrians without interfering the traffic, an elevated walkway is built to connect the library with other buildings around the roundabout. The walkway consists of steel frames and concrete piers.